Mesenchymal stem cells participate to inflammatory skin process of atopic dermatitis. (1st June 2017) - Balato, A.; Caiazzo, G.
Abstract: Linked Article: Orciani et al . Br J Dermatol 2017; 176 :1569–1576 .